2015
DOI: 10.1111/pme.12688
|View full text |Cite
|
Sign up to set email alerts
|

Transaction Cost Analysis of In-Clinic Versus Telehealth Consultations for Chronic Pain: Preliminary Evidence for Rapid and Affordable Access to Interdisciplinary Collaborative Consultation

Abstract: Objectives With ever increasing mandates to reduce costs and increase the quality of pain management, health care institutions are faced with the challenge of adopting innovative technologies and shifting workflows to provide value-based care. Transaction cost economic analysis can provide comparative evaluation of the consequences of these changes in the delivery of care. The aim of this study was to establish proof-of-concept using transaction cost analysis to examine chronic pain management in-clinic and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…Specialities represented by less than three papers in total (n=11) were grouped under 'others' in Table 4. These included the following specialities: Hematology, Otolaryngology, General Medicine, Geriatric, Nephrology, Obstetrics, and Orthopaedics (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specialities represented by less than three papers in total (n=11) were grouped under 'others' in Table 4. These included the following specialities: Hematology, Otolaryngology, General Medicine, Geriatric, Nephrology, Obstetrics, and Orthopaedics (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Resultsmentioning
confidence: 99%
“…Simple cost analysis was used by (n=14) (52,(63)(64)(65)(66)(67)(70)(71)(72)(73)(74)(75)(76)(77) studies measuring the cost avoidance, cost saving and added revenue. While (n=15) (27,30,35,58,68,69,(78)(79)(80)(81)(82)(83)(84)(85)(86) studies conducted a cost minimization analysis as a method to assess the economic benefits of telemedicine. The cost of providing telemedicine services was compared to the cost of providing the same healthcare service in a conventional face-to-face manner, whether it was a hospital based visit where the patient travels to get the service, or an outreach clinic where the provider travels to provide the care.…”
Section: Economicmentioning
confidence: 99%
“…For example, the Specialty Care Access Network-ECHO pain management program (SCAN-ECHO-PM) provided primary care providers with case-based pain management specialist consultation that led to increased utilization of physical medicine services and initiation of nonopioid analgesics for patients in the Veterans Health Administration [18]. Another study demonstrated rapid and cost-effective access of telehealth consultation visits between primary care providers in Washington State and a team of pain medicine specialists compared with 'in-clinic visits,' as it pertains to transaction cost analysis [19]. In our study, the quality of care was maintained via direct videoconferences with patients and pain specialists, physical exams performed by appropriately trained nursing staff, and monthly physician visits to the island for procedural interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The value of pain management telementoring programs is supported by several studies, with demonstrations of increased provider knowledge and/or confidence, 2 , 5 , 31 , 53 , 67 improved communication between patients and providers, 5 , 17 greater guideline adherence, 2 and cost benefits relative to specialty clinic visits. 85 Systemic changes (eg, leadership buy-in and modified clinic schedules) that increase the feasibility of regular participation in telementoring may be necessary. 29 , 75 Another E-learning approach for providing structured training and mentored practice of psychologically informed methods for providers to enhance pain self-management by patients with chronic pain involves online webinar-style interactive sessions with skills practice required between sessions.…”
Section: Advancing Telehealth-delivered Pain Care Through Researchmentioning
confidence: 99%